Regulation, emissions and productivity: Evidence from China's Eleventh Five-Year Plan - Brantly Callaway; Tong Li; Joel Rodrigue; Yuya Sasaki; Yong Tan (Bank of Canada, 2024)
Leveraging the sharp changes in environmental regulation embedded in China's 11th Five-Year Plan (FYP), which covered the period from 2006 to 2010, we characterize the degree to which the plan softens trade-offs between emissions and output. We document that the 11th FYP is associated with modest changes in average or total sulphur dioxide (SO2) emissions among manufacturers, but a sharp decline in the variance in the distribution of emissions intensity. Extending well-known distributional estimators to characterize dynamic firm-level responses to policy change, we find large causal declines in emissions intensity in the upper quantiles of the distribution, modest evidence of increases in the lower quantiles and no change in the middle quantiles. Differential changes in firm-level emissions intensity are consistent with the differential investment in emissions-mitigating technology, energy switching and productivity improvements. Interpreted through the lens of a resource misallocation framework, China's 11th FYP increased aggregate productivity and output by 1.8% and 10.2%, respectively, through improved resource allocation. Our model suggests efficient regulation could have further increased aggregate productivity by 3.5% and output by 4.7% without any increase in aggregate emissions.
Keywords: C21; D24; Q53; 330; Climate change; Productivity